Development NGOs facing the 21st century : perspectives from South Asia - Vartola, Juha.; Institute for Human Development (Kathmandu, Nepal) (Kathmandu : Institute for Human Development, 2000)
Contributed articles.
Includes bibliographical references.
Keywords: Non-governmental organizations -- South Asia; South Asia -- Economic policy